(untitled) (Perner’s Contacts, 2022)
The paper deals with the issue of professional competence to operate road transport for extraneous needs by "large vehicles" (heavy goods vehicles and buses). Regulations of the European Union valid for this area are presented and commented. The paper also presents and compares how this issue is regulated in specific conditions of the Czech Republic and the Slovak Republic. It analyses the availability of information and information sources for exam preparation. It also analyses the conditions, the technological procedure, the content, and the evaluation of the examination test. It proposes modifications with an effort to simplify the administration and to improve the availability of information on the application, the process, and the evaluation of the examination. The aim of the paper is to improve the clarity and quality of the preparation as well as of the examination process in the field of professional competence in road transport for operation of heavy goods vehicles and buses for extraneous needs.